Analysis of the Influence of the Tourism Sector on Original Regional Income (PAD) in Minahasa Regency for the 2008-2022 Period - Ratuela, Celvin Friskie; Maramis, Mauna Th. B.; Mandeij, Dennij (PT FORMOSA CENDEKIA GLOBAL, 2024)
Objective: To find out how many hotels, restaurants and returning visitors contribute to the regional income of Minahasa Regency in 2008–2022 is the aim of this research. The Minahasa Regency Tourism and Culture Office and the Central Statistics Agency provided time series data which is a type of secondary data used in this research. One type of analysis method is multiple linear regression analysis. Research findings show that the initial regional income of Minahasa Regency is greatly influenced and profitable by the number of visitors. In Minahasa Regency, the number of hotels has a negative and very large impact compared to local revenue. In Minahasa Regency, the amount of income in the area is influenced significantly and profitably by restaurants. During 2008–2022, the large number of hotels, restaurants and tourists had a major impact on the local economy in Minahasa Regency.